Is it premature to formulate recommendations for policy and practice, based on culture and health research? A robust critique of the CultureForHealth (2022) report - Kaasgaard, Mette; Grebosz-Haring, Katarzyna; Davies, Christina; Musgrave, George; Shriraam, Jahnusha; McCrary, J. Matt; Clift, Stephen (Frontiers in Public Health, 2024)
Introduction: Arts and health practice and research has expanded rapidly since the turn of the millennium. A World Health Organization scoping review (WHO, 2019) of a large body of evidence claims positive health benefits from arts participation and makes recommendations for policy and implementation of arts for health initiatives. A more recent scoping review (CultureForHealth, 2022) also claims that current evidence is sufficient to form recommendations for policy and practice. However, scoping reviews of arts and health research -without critical appraisal of included studiesdo not provide a sound basis for recommendations on the wider implantation of healthcare interventions. Methods: We performed a detailed assessment of 18 Randomised Controlled Trials (RCTs) on artsbased interventions included in Section 1 of the CultureForHealth report using the Joanna Briggs Institute Critical Appraisal Tool for RCTs (2023).The 18 RCTs included demonstrated considerable risks of bias regarding internal and statistical conclusion validity. Moreover, the trials are substantially heterogeneous with respect to settings, health-issues, interventions, and outcomes, which limits their external validity, reliability, and generalisability. Conclusions: The absence of a critical appraisal of studies included in the CultureForHealth report leads to an overinterpretation and overstatement of the health outcomes of arts-based interventions. As such, the CultureForHealth review is not a suitable foundation for policy recommendations, nor for formulating guidance on implementation of arts-based interventions for health.